CSF synaptic biomarkers and cognitive impairment in multiple sclerosis - Barba, Lorenzo; Gaetani, Lorenzo; Sperandei, Silvia; Di Sabatino, Elena; Abu-Rumeileh, Samir; Halbgebauer, Steffen; Oeckl, Patrick; Steinacker, Petra; Parnetti, Lucilla; Di FIlippo, Massimiliano; Otto, Markus (Journal of neurology, 2025)
Background People with multiple sclerosis (PwMS) experience various degrees of cognitive impairment (CI). Synaptic dysfunction may contribute to CI in PwMS but cerebrospinal fluid (CSF) synaptic biomarkers are unexplored in MS. Objective To assess the role of CSF synaptosomal-associated protein 25 (SNAP-25), β-synuclein, neurogranin and neurofilament light chain protein (NfL) in patients with early relapsing MS with and without CI. Methods We measured CSF SNAP-25, β-synuclein, and neurogranin in 48 untreated PwMS and 50 controls with other neurological diseases (ONDs) and tested their associations with neuropsychological and MRI data. Results CSF synaptic protein levels did not discriminate between MS subjects and patients with ONDs, with only SNAP-25 values being slightly increased in MS ( p = 0.009). CSF synaptic markers were positively correlated with each other and with CSF NfL. Moreover, lower biomarker levels were found to be correlated with longer disease duration and lower brain volumes (especially of the thalamus). Moreover, we found significantly lower CSF SNAP-25 ( p = 0.025), β-synuclein ( p = 0.044), and neurogranin ( p = 0.007) levels in PwMS with vs. without domain-specific cognitive impairment. Conclusion Lower CSF synaptic biomarker levels were found in PwMS with longer disease duration and lower brain volumes and may identify PwMS at risk of CI.